Adult QRIS User Experience in Digital Payment Systems: A Phenomenological Study in Gandus District, Palembang City - Ridho Elrazy; Safira Elfadhilah; Siti Zailia; , KM Badaruddin (Takaza Innovatix Labs Ltd., 2026)
The development of digital payment systems in Indonesia has led to the implementation of QRIS as a more practical and efficient transaction solution; However, its application still faces several challenges in society. This study aims to analyze users' experiences in using QRIS, focusing on aspects of convenience and ease of use, motivation for adoption, and existing obstacles. This research employed a qualitative phenomenological approach through in-depth interviews with ten informants from various occupational backgrounds. The findings indicate that QRIS provides significant benefits in terms of convenience, speed, efficiency, and perceived security, thereby encouraging behavioral shifts toward digital payments. Nevertheless, several challenges were identified, including network instability, system constraints, uneven digital literacy, device readiness, and trust issues. The implications highlight the importance of strengthening digital infrastructure, enhancing user education, and optimizing system reliability to support sustainable QRIS usage in society.